Intestinal Permeability: The Basics. (1st June 1995) - Bjarnason, Ingvar; Macpherson, Andrew; Menzies, Ian S
Abstract : The authors review some of the more fundamental principles underlying the noninvasive assessment of intestinal permeability in humans, the choice of test markers and their analyses, and the practical aspects of test dose composition and how these can be changed to allow the specific assessment of regional permeability changes and other intestinal functions. The implications of increased intestinal permeability in the pathogenesis of human disease is discussed in relation to findings in patients with Crohn's disease. A common feature of increased intestinal permeability is the development of a low grade enteropathy, and while quantitatively similar changes may be found in Crohn's disease these seem to predict relapse of disease. Moreover, factors associated with relapse of Crohn's disease have in common an action to increase intestinal permeability. While increased intestinal permeability does not seem to be important in the etiology of Crohn's disease it may be a central mechanism in the clinical relapse of disease.